Kompetensi Kepribadian Dan Bahasa Santun Guru Pendidikan Agama Islam - Rafly Billy Limnata; Hilalludin Hilalludin; Adi Haironi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This study explores the critical role of teachers as role models in shaping student character through personal competence and linguistic politeness. Quality teachers are evaluated not only based on their academic qualifications but also their mental stability, intellectual capacity, professionalism, and religious morality. School principals play a key role in developing effective educational systems by focusing on the cultivation of teachers' personal competence. Personal competence includes emotional stability, maturity, wisdom, authority, and noble character. Additionally, the linguistic politeness employed by teachers in daily communication can create a conducive and harmonious learning environment. This research employs a literature review method, collecting data from various literature sources. The results indicate that teachers' personal competence and linguistic politeness significantly influence students' learning motivation. Teachers who serve as role models in behavior and communication can enhance students' motivation and enthusiasm for learning. Therefore, the development of personal competence and linguistic politeness should be a focus in teacher training programs to achieve holistic and sustainable educational goals.